2019
DOI: 10.1038/s41598-018-36803-4
|View full text |Cite
|
Sign up to set email alerts
|

Macaque monkeys learn by observation in the ghost display condition in the object-in-place task with differential reward to the observer

Abstract: Observational learning has been investigated in monkeys mainly using conspecifics or humans as models to observe. Some studies attempted to clarify the social agent’s role and to test whether non-human primates could learn from observation of a non-social agent, usually mentioned as a ‘ghost display’ condition, but they reported conflicting results. To address this question, we trained three rhesus monkeys in an object-in-place task consisting of the presentation of five subsequent problems composed of two obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 49 publications
(83 reference statements)
0
17
0
Order By: Relevance
“…Had we found differences between the individual and social conditions, the animated cue condition would have assisted in examining the possible underlying mechanisms. The finding of non-differentially effective information use from an animated cue condition and a social condition by task-proficient monkeys and children is unusual, given that a number of previous studies have shown impoverished learning from ghost conditions 8 13 , 41 43 , but see 14 . It is possible that the difference between this study and the others is due to participants engaging in multiple trials, with corresponding opportunities to learn the game’s strategy.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Had we found differences between the individual and social conditions, the animated cue condition would have assisted in examining the possible underlying mechanisms. The finding of non-differentially effective information use from an animated cue condition and a social condition by task-proficient monkeys and children is unusual, given that a number of previous studies have shown impoverished learning from ghost conditions 8 13 , 41 43 , but see 14 . It is possible that the difference between this study and the others is due to participants engaging in multiple trials, with corresponding opportunities to learn the game’s strategy.…”
Section: Discussionmentioning
confidence: 98%
“…Generally, to compare the performance of humans and non-human primate species in tasks that involve social learning, researchers provide participants with varying amounts of information about how to solve the task. End-state conditions show a “solved” problem or apparatus 4 7 ; ghost conditions provide some information about object movement or other causal relation 7 14 ; and full social demonstrations show an agent’s body movements as well as changes to an apparatus 4 16 . If the outcome achieved by the social demonstrator is repeated at a higher rate than outcomes revealed or shown in some other way, researchers usually conclude that social information has been given priority over other sources.…”
Section: Introductionmentioning
confidence: 99%
“…These correct response rates and the low rate of aborted trials in after-computer trials together indicate that the monkeys were able to remain focused for most of the session. This discrepancy between studies (in terms of information extraction from the host agent) may be accounted for by the delivery of a reward to the monkey, which did not occur in the study of Subiaul et al 57 , as previously suggested by Ferrucci et al 44 .…”
Section: Discussionmentioning
confidence: 67%
“…Different cognitive functions investigated in neurophysiological experiments require pre-training to execute more than just single trials in isolation, although this is rarely mentioned. For example, different behavioral tasks used to study the generation of goal-directed rules and responses 60,61 , logical reasoning 62 , mapping of stimulus-response associations 63 , and one-trial learning 44,64 require monkeys to constantly take into account various task variables learned in previous trials and carry out subsequent trials during the session, so that the neural correlates involved can be studied. In addition, a common approach in electrophysiology consists of requiring the monkey to repeat the same behavior several times and recording the neural activity during this behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation